2016
DOI: 10.2119/molmed.2015.00182
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Ergotope Peptides on Collagen-Induced Arthritis by Downregulation of inflammatory and Th1/Th17 Responses and Induction of Regulatory T Cells

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune disease that results in a chronic and inflammatory disorder. Dynamic balance of helper T cells (Th) 1 and 17 and regulatory T cells (Treg) is broken in RA. Since there is no cure for RA at present, it is necessary to find a truly effective and convenient treatment. Several studies have intended to induce ergotopic regulation to treat autoimmune diseases. This study was undertaken to find potential ergotope peptides and investigate their effects in treating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Efficient and specific targeting of either Th1 or Th17 or, more likely, both Th1 and Th17 cells, may prove potentially therapeutic for suppression of inflammatory diseases, including uveitis. Additionally, the contribution of double-positive so-called "intermediate Th1/Th17 cells" has also been reported in the pathogenesis of inflammatory diseases (54)(55)(56). Interestingly, levels of double-positive IFN-g/IL-17-expressing pLN T cells from EAU mice were also decreased following treatment with BET inhibitors, and their function was suppressed in response to BET inhibition in vitro, supporting the hypothesis that BET inhibitors target pathogenic T cells in EAU.…”
Section: Discussionmentioning
confidence: 60%
“…Efficient and specific targeting of either Th1 or Th17 or, more likely, both Th1 and Th17 cells, may prove potentially therapeutic for suppression of inflammatory diseases, including uveitis. Additionally, the contribution of double-positive so-called "intermediate Th1/Th17 cells" has also been reported in the pathogenesis of inflammatory diseases (54)(55)(56). Interestingly, levels of double-positive IFN-g/IL-17-expressing pLN T cells from EAU mice were also decreased following treatment with BET inhibitors, and their function was suppressed in response to BET inhibition in vitro, supporting the hypothesis that BET inhibitors target pathogenic T cells in EAU.…”
Section: Discussionmentioning
confidence: 60%
“…To assess the therapeutic effect of these DCs with tolerogenic profiles, we next used an animal model equivalent to rheumatoid arthritis, an autoimmune pathology involving a relevant role of DCs in the induction of Th1- and Th17-mediated inflammation [47]. Accordingly, we use the mouse model of CIA, which involves an autoimmune response to collagen driven by autoreactive Th1 and Th17 lymphocytes [26]. To this end, STAT3ca-transduced DCs or I κ B α SR-transduced DCs were loaded with type II collagen (CII) as an autoantigen, and then intravenously administered in mice undergoing CIA, and the disease severity was determined by scoring the extent of inflammation of mouse paws (Figure 1(e)) throughout the time course of the disease development.…”
Section: Resultsmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic autoimmune disorder occurring in about 5% of the general population, leading to severe joint damage and disability [24]. Previous evidence has shown that Th1 and Th17 cells are the phenotypes of autoreactive CD4 + T-cells involved in RA and its mouse model, the type II collagen-induced arthritis (CIA) [25, 26]. Of note, due to that functional phenotype of DCs represents a key factor in the decision to promote tolerance or inflammation in response to specific antigens, the usage of autologous tolerogenic DCs loaded with autoantigens as therapy for the treatment of RA has been recently tested in phase I clinical trials and proven to be safe [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…IL-2Rɑ is a subunit of IL-2R, which is specific for IL-2R (31). IL-2Rɑ reportedly regulates the Treg/Th17 ratio (32) and is associated with rejection in tissue transplant patients (33,34). Therefore, we focused on the miR-151-5p/IL-2Rɑ axis for detailed research into their roles in CGR of CT.…”
Section: Integrated Analysis Of Differentially Expressed Mirna and Mrnamentioning
confidence: 99%